Evaluating the effect of BDNF Val66Met polymorphism on complex formation with HAP1 and Sortilin1 via structural modeling. (February 2019) - Zamani, Mozhdeh; Eslami, Mahboobeh; Nezafat, Navid; Hosseini, Seyed Vahid; Ghasemi, Younes
Graphical abstract: Highlights: BDNF has a vital role in neurogenesis, differentiation, survival of the neurons, regulation of the appetite. Val66Met substitution of proBDNF affects the interaction of proBDNF with HAP1 and Sortilin1 proteins. Structural studies indicated that Val66Met polymorphism leads to instability of proBDNF-HAP1 and proBDNF-Sortilin1 complexes. Abstract: Brain derived neurotrophic factor (BDNF) has a critical role in the neurogenesis, differentiation, survival of the neurons, regulation of the appetite, and energy homeostasis. Two key proteins, Huntingtin associated protein-1 (HAP1) and sortilin1, regulate the intracellular trafficking and stabilization of the precursor proBDNF through interaction with its prodomain region and mark it for secretion. Evidence suggests that the most frequent single nucleotide polymorphism (SNP) of BDNF gene (rs6265) has been associated with different psychiatric, neurodegenerative and eating disorders. In this study, structural bioinformatics and molecular dynamics (MD) simulations were applied, in order to get precise insights into the impact of Val66Met polymorphism on the proBDNF structure and its interaction with HAP1 and Sortilin1. Homology modeling, structure validation, refinement and also protein-protein docking were performed using appropriate servers. The stability, the fluctuations and the compactness of protein complexes were measured by MD simulation parameters including root mean square deviation (RMSD), root mean square fluctuation (RMSF) and Radius of gyration (Rg), respectively. The mutant proBDNF complexes with HAP1 and Sortilin1 revealed higher RMSD and RMSF values and also variable Rg over time compared with wild-type proBDNF. These computational results indicated that, wild-type proBDNF possessed more stable structure in binding with HAP1 and Sortilin1 compared with its mutant form. Therefore, Val66Met SNP could be deleterious due to making structural changes. It may cause a decrease in proBDNF secretion, which could possibly lead to different psychiatric, neurodegenerative and eating disorders. Further experimental lab studies are required for a more accurate conclusion.